Liver regeneration after partial hepatectomy: effects of glucose and branched-chain amino acid - Lai, H S; Chen, W J; Chen, K M (Journal of the Formosan Medical Association, 1990)
The phenomenon of liver regeneration has been observed within several days after partial hepatectomy, though there is still much controversy as to its initiation, regulation, and the control factors behind it. Male Wistar rats weighing around 200 g were used as subjects in this study. Partial hepatectomy with resection of the median and left lateral lobes (67.31%) was performed. High glucose, low glucose, or high or low branched-chain amino acid (BCAA) solutions were given intravenously 2 days prior to the partial hepatectomy. The rats were sacrificed at 6, 24, 48, and 72 hours after the operation. Remnant liver weight, Deoxyribonucleic acid (DNA) content, DNA synthesis rate, and mitotic index were chosen as markers for comparing the effects of the glucose and branched-chain amino acid solutions on liver regeneration. The results were as follows: (1) following removal of two-thirds of a rat's liver, DNA synthesis increased abruptly, peaking at 24 hours, the mitotic index reached a maximum at 48 hours, and the remaining lobes had doubled in size by 48 hours and had attained around 90% of the normal liver weight at 72 hours; (2) judging by the results of the remnant liver weight, DNA content, and DNA synthesis rate, the low glucose infusion rates showed the worst regenerative condition; and (3) the only effect of BCAA on liver regeneration observed was that low BCAA infusion rates resulted in a lower DNA content in the remnant liver.